Human epidermal growth factor receptor 2 overexpression and amplification in endoscopic biopsies and resection specimens in esophageal and junctional adenocarcinoma. Issue 4 (10th March 2014) - van Hagen, P.; Biermann, K.; Boers, J. E.; Stoss, O.; Sleddens, H. F.; van Lanschot, J. J. B.; Dinjens, W. N. M.; Rueschoff, J.; Wijnhoven, B. P. L.
Summary Human epidermal growth factor receptor 2 (HER2) is overexpressed in a subset of esophageal adenocarcinomas. Frequently, biopsy material is used for evaluation of HER2 status. The aim of the study was to determine if HER2 expression in preoperative endoscopic biopsies is representative for the entire tumor. Preoperative endoscopic biopsies and matched resection specimens were collected from 75 patients who underwent esophagectomy for esophageal adenocarcinoma. Immunohistochemical staining (IHC) on HER2 and dual‐color in situ hybridization (ISH) were performed. HER2 status was determined by following a clinical algorithm, first determining HER2 overexpression on immunohistochemistry and, when equivocal (2+), determining HER2 amplification on ISH. Seventy‐one of 75 (95%) biopsies and 69/75 (92%) resection specimens could be analyzed due to technical failure. HER2 positivity was seen in 18/71 (25%) biopsies and in 15/69 (22%) resection specimens. Overall, HER2 status in the biopsy was concordant with HER2 status in the resection specimen in 94% of cases. Interobserver agreement on IHC scoring for all three observers was 83% in biopsies and 85% in resection specimens. HER2 positivity was detected in 22% of esophageal adenocarcinomas. Although interobserver agreement was moderate, HER2 status of a primary tumor can be reliably determined based on the endoscopically obtained pretreatment biopsy.